Chemical amination of lipases improves their immobilization on octyl-glyoxyl agarose beads - Rueda, Nazzoly; Dos Santos, José C. S.; Ortiz, Claudia; Barbosa, Oveimar; Fernández-Lafuente, Roberto; Torres Sáez, Rodrigo (Catalysis Today, 2016)
This paper describes a new strategy that permits to take full advantage of octyl-agarose supports to immobilize lipases (one-step purification and immobilization, stabilization of the open form of the enzyme) but that may be used in any reaction media. To this purpose, we have utilized aminated lipases and glyoxyl-octyl agarose (OCGLX). As model enzymes, we have used lipase B from Candida antarctica, lipase from Thermomyces lanuginosus and lipase from Rhizomucor miehei (RML). The amination of the enzyme may be performed in the enzymes already adsorbed on OCGLX, greatly simplifying the protocol. The immobilization was carried out at pH 5 to ensure the immobilization via interfacial activation versus the hydrophobic support, and afterwards the pH was increased to pH 9 or 10 to promote some covalent attachments. 100% of the aminated lipases became covalently immobilized on OCGLX after 2 h even at pH 9, while using unmodified enzymes some enzyme molecules could be desorbed from the support even after 24 h of incubation at pH 10, with a significantly lower cost in terms of activity. The resulting biocatalysts have a significant improved stability compared to the non-aminated OCGLX preparations. Amination in some instances presented positive effects on enzyme properties, while in other cases the effects were negative. However, the covalent immobilization at OCGLX compensated the negative effects and increases the positive ones. In some cases, the stabilization factor become 40–50 when compared with the use of non-aminated enzyme (e.g., using RML), and retained a high percentage of hydrolytic activity in the presence of acetonitrile concentration as high as 90%, where the enzyme immobilized on octyl supports could be desorbed. We gratefully recognize the support from the MINECO of Spanish Government, CTQ2013-41507-R. The predoctoral fellowships for Ms. Rueda (Colciencias, Colombian Government) and Mr. dos Santos (CNPq, Brazil) are also recognized. The authors wish to thank Mr. Ramiro Martínez (Novozymes, Spain) for ...